2002
DOI: 10.1078/0944-5013-00169
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ferrous iron to maintenance of the gastric colonization of Helicobacter pylori in miniature pigs

Abstract: Our previous study showed that the colonization levels of Helicobacter pylori were higher in the stomachs of 5-day-old miniature pigs than in 2-week-old ones. As dietary factors can cause these differences, we compared two diets, i.e., Weanymilk and a similar formula with a higher concentration of Fe(II), Weanylobulin. The colonization levels in the fundic mucosa were significantly higher in 2-week-old pigs fed Weanylobulin than in those fed Weanymilk. Supplementing Weanylobulin with an iron chelator, deferoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The requirement for ample amounts of dietary iron is supported by an in vivo study by Koga and colleagues (12). Those authors found that improved colonization of piglets by H. pylori occurred when the animals' diet was supplemented with additional iron (12). The high-iron requirement of H. pylori could also explain why this organism does not colonize the intestine, where other bacterial species would rapidly scavenge iron.…”
Section: Discussionmentioning
confidence: 97%
“…The requirement for ample amounts of dietary iron is supported by an in vivo study by Koga and colleagues (12). Those authors found that improved colonization of piglets by H. pylori occurred when the animals' diet was supplemented with additional iron (12). The high-iron requirement of H. pylori could also explain why this organism does not colonize the intestine, where other bacterial species would rapidly scavenge iron.…”
Section: Discussionmentioning
confidence: 97%
“…Although, there are differences between naturally occurring gastric ulcers between pigs and humans, the pig represents an interesting animal model to study the repair of gastric ulcers (KOGA et al, 2002;PADRA et al, 2018;BANG et al, 2019;MAEDA et al, 2019), and the pathogenic mechanisms involved in their formation, mainly with Helicobacter pylori (POUTAHIDIS et al, 2001). Pigs have systemic similarities with humans and a suitable profile for biomedical research (GIANOTTI et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…[161][162][163][164][165][166][167][168] However, inflammation and gastritis were observed in the early stages of H. pylori infection (below 1 year). [160][161][162][163][164][165][166][167][169][170][171][172][173] Still, after 5 years of H. pylori inoculation, Neoplasia was observed. 168 Besides nonhuman primates, pigs were also used as an animal model in gastric cancer research, and they showed diverse pathological outcomes due to H. pylori infection.…”
Section: Other Animalsmentioning
confidence: 99%